SWOT Analysis of Housing Co-operatives in South Africa - Jimoh, R.A.; Van Wyk, J.J. (Civil Engineering Dimension, 2014)
While South Africa has the necessary legislative and policy frameworks in housing and other sectors that could have contributed to the development of co-operative housing approach, little is done to promote it. To that end, this paper provides the SWOT (Strength, Weaknesses, Opportunities and Threats) analysis of 6 housing co-operatives in South Africa. Based on the data generated from the multi-case study conducted and the administration of self addressed questionnaires, a SWOT analysis was done in order to identify the strengths, weaknesses, opportunities and threats to the housing co-operatives, with a view to developing sustainable strategies. Results from the study shows that the housing co-operatives are faced with many threats arising from the external environment and many weaknesses arising from the inadequate internal resources and circumstances. One of the strategies proposed is that there should be formulation and implementation of appropriate policies and legislation beneficial to the housing co-operatives by the government.